Income Convergence and the Flow out of Poverty in India, 1994-2005 - Paola Andrea Barrientos Quiroga; Niels-Hugo Blunch; Nabanita Datta Gupta (Institute for the Study of Labor (IZA), 2015)
This paper explores the dynamics of income and poverty of rural Indian households, 1994-2005. The estimation strategy consists of convergence analysis to test whether poor households are catching-up in terms of income, followed by transition analysis to test whether poor households are more likely to exit poverty than to remain poor. The identification strategy explicitly addresses issues pertaining to the potential endogeneity and measurement error of initial income and poverty. We find evidence of income convergence and a higher probability of exiting poverty than of remaining poor. The key variables driving these results are education, occupation and asset ownership.
Keywords: O12; O47; O53; 330; income convergence; poverty transition; endogeneity; measurement error; IHDS & HDPI data